PENGARUH SOSIALISASI, TINGKAT PENDIDIKAN, PERSEPSI PELAKU USAHA, PEMAHAMAN AKUNTANSI DAN MOTIVASI KERJA TERHADAP PENERAPAN PENYUSUNAN LAPORAN KEUANGAN EMKM - Anisa Zerlina; Alfiati Silfi; Eka Hariyani (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2023)
This EMKM business can be done by anyone, but there are still many EMKM actors who neglect to make financial reports in accordance with the applicable SAK. Therefore, information regarding accounting is needed which can be obtained from electronic media or reading books on accounting specifically for EMKM so that EMKM actors can easily compile relevant financial reports, can be compared and understood by anyone. Accounting plays an important role in the progress of EMKM and every business is expected to have financial reports to analyze financial performance so as to provide information about the company's financial position, financial performance and cash flow that is useful for making decisions for users of financial statements. In this study, the population of EMKM was 15,126 and the sample used the slovin formula was 100 EMKM. The data analysis method used in this study is a quantitative data analysis method. The test results show that the socialization and work motivation has no effect on the application of SAK EMKM. The level of education has an effect on the application of SAK EMKM, the perception of business actors has an effect on the application of SAK EMKM, accounting understanding has an effect on the application of SAK EMKM.